PENINGKATAN KEMAMPUAN MENULIS MELALUI PERMAINAN MENGGAMBAR (PENELITIAN TINDAKAN DI KELOMPOK B TAMAN KANAK-KANAK SOS DESA TARUNA JAKARTA TIMUR) - Ambar Pawitri (JECIES: Journal of Early Childhood Islamic Education Study, 2020)
The aims of this research are to know the ability to write in early childhood through drawing games. The research was conducted through action research in group B kindergarten SOS Desa Taruna. The study is conducted using action research and held from May to June the second semester. The procedures for this action research are following Kemmis and Taggart’s model consisting of four phases cycle which is (a) planning, (b) action, (c) observation, (d) reflection. Data analysis is carried using both quantitative and qualitative by the positive response of drawing games. In the 1st cycle, early childhood writing ability is…% and early childhood writing ability increasing…% in the 2nd cycle. The implication of the research finding, drawing games should be children learn writing ability with fun but can make children study writing, drawing games it should be an alternative to teach writing for the children.